1978
DOI: 10.1007/bf00266914
|View full text |Cite
|
Sign up to set email alerts
|

UV-inducible repair II: Its role in various defective mutants of Escherichia coli K-12

Abstract: Involvement of UV-inducible protein(s) in repair of various E. coli K-12 cell strains has been investigated using a procedure of double UV irradiation and postincubation with chloramphenicol. From the course of dose survival curves the following conclusions concerning significance of a UV-inducible protein have been drawn: 1. It is a very important for wild type cells; in these cells its early occurrence is necessary to prevent killing. 2. It is involved in repair of excision-deficient cells; however, its acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Further characterization indicated that the lac fusion was indeed to the uvrA gene, and thus that at least one of the SOS-regulated loci identified by this procedure actually coded for a gene product (172). The observation that the uvrA gene was inducible was consistent with a series of in vivo observations indicating that uvr+-dependent repair processes can be induced in E. coli (57,58,319,320).…”
Section: Downloaded Fromsupporting
confidence: 77%
“…Further characterization indicated that the lac fusion was indeed to the uvrA gene, and thus that at least one of the SOS-regulated loci identified by this procedure actually coded for a gene product (172). The observation that the uvrA gene was inducible was consistent with a series of in vivo observations indicating that uvr+-dependent repair processes can be induced in E. coli (57,58,319,320).…”
Section: Downloaded Fromsupporting
confidence: 77%
“…The process in question is a complex one. Previous data (Sedliakova' et al, 1978b) appear to indicate that it requires at least four genes to function, namely, uvrA, uvrB, lexA and recA.…”
Section: Discussionmentioning
confidence: 93%
“…Our results demonstrate that the DNA damage-inducible SOS response plays a role in upregulating NER capacity in E. coli. The existence of such an upregulation after DNA damage has been previously postulated for several reasons, including (i) the demonstration that uvrA, uvrB, and uvrD were under Rec/Lex control and were induced rapidly after DNA damage (1,18,24,38); (ii) the dramatic increase in phage (5,48) and bacterial (5,12) survival if cells were preinduced by low flu- ences of UV or by genetic means; (iii) the reduced rate of CPD repair in recA mutants and the subsequent rapid rate of CPD repair when the SOS response was derepressed in the same cells (12); and (iv) the decrease in cell survival when protein synthesis treatments were given immediately following UV (13,39,40).…”
Section: Discussionmentioning
confidence: 99%